INCORPORATING THE CANVA APPLICATION AS LEARNING MEDIUM IN TEACHING DESCRIPTIVE TEXT WRITING SKILL AT SENIOR HIGH SCHOOL - Sabila Khoerun Nisa; Mobit Mobit; Acep Bahrum Kamil (PROJECT (Professional Journal of English Education), 2024)
In the growing digital era, the use of technology in the learning process is very important to increase students' learning motivation. This study aims to investigate factors influencing students' difficulties in writing descriptive text and to find out students' responses to the use of the Canva application as a medium for learning writing in senior high school. This research uses a case study method with a qualitative approach. The subjects of this study were students of class X MIPA 5 at a high school in Karawang. Data were collected through observation, questionnaires, interview, and document analysis of students' work. In the interview, the researcher involved 5 students. The results showed that students gave positive responses to the use of Canva as a learning medium for writing descriptive text.